ANALISA RELIABILITY, MAINTAINABILITY DAN AVAILABILITY UNTUK MENINGKATKAN EFEKTIVITAS DAN EFESIENSI STERILIZER DI PABRIK KELAPA SAWIT - Zulham Effendi; Ika Ucha Pradifta Rangkuti (Jurnal Agro Estate, 2017)
Palm Oil Millprocessingfreshfruit bunches (FFB) into palm oil andpalm kernel. In an effort to maintain quality and improve productivity, one ofthefactors that must be considered is theproblem ofmaintenance of the facilities / production machine. This study discusses the causes and consequences caused by the breakdown occurred Sterilizer machine, particularly on HorizontalSterilizer and vertical Sterilizer. To get a machine that can be maintained keterandalannya needed a good concept. Total Productive Maintenance (TPM) is a good concept to realize this. This concept, in addition to involving all personnel in the company, also aims to take care ofall the production facilities ofthe company. The data used is the data breakdown Horizontal Sterilizer and Vertical Sterilizer during the months from July to September 2015. In addition, this study also discusses the performance ofmaintenance mills, taking into account the value Mean Time beetwen Failure (MTBF), Mean Time To Repair (MTTR), and availability machine, using data from the foreman daily recordfor the month ofJuly 2015 until September 2015. So that later will know the actual state o f the company's information about treatment systems, especially in Sterilizer whether good or bad. Horizontal Sterilizerresearch results in July availablity value of99.50%, 0.42 hours maintainability and reliability value of283.75 hours while Vertical Sterilizerseptember availablity value of 98%, the value o f the maintainability o f 1.7 hours and 126.95 hours reliability value indicating reliability good, availability andperformance meets the standard ofthe lower maintenance operator will be well andgood.